Mechanisms of increased Trichodesmium fitness under iron and phosphorus co-limitation in the present and future ocean - Nathan G. Walworth (Nature Portfolio, 2016)
Cyanobacterial nitrogen fixation supplies bioavailable nitrogen to marine ecosystems, but the mechanisms governing iron and phosphorus co-limitation in elevated CO2remain unknown. Here, the authors show a complex cellular response to co-limitation characterized by changes in growth, cell size, and the proteome.